Curbing Nuclear Latency: How International Norms Promote Benign Nuclear Assistance - Kim, Lami. (Tufts University. Tisch Library., 2019)
Does civil nuclear assistance increase the risk of nuclear proliferation? Previous scholarship suggests a positive correlation between civil nuclear assistance and nuclear weapons proliferation. However, a close scrutiny reveals that this theory explains only the first half of the nuclear era but not afterwards. Why did civil nuclear assistance facilitate the development of nuclear weapons in some cases but not in others? My dissertation demonstrates that the answer lies in the multilateral nuclear export control regime that emerged in the mid-1970s. The nuclear export environment has changed dramatically since the Nuclear Suppliers Group (NSG) established restrictions over sensitive nuclear assistance, which allows recipients to achieve "nuclear latency" in the mid-1970s. Since then, sensitive nuclear assistance has significantly decreased and so has the proliferation risks involving civil nuclear assistance. Drawing on institutionalism, constructivism and discursive theory, I argue that the NSG has made states refrain from sensitive nuclear assistance by raising the costs of such assistance, on one hand, and strengthening the benefits accrued by refraining from it, on the other. The NSG has succeeded not only by forcing states to act within the boundary of justifiable behavior under NSG norms, but also by socializing states into embracing these norms. In order to find empirical evidence, my dissertation employs qualitative case studies of France, West Germany and China, based on archival materials, interviews and secondary sources.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of International Law and Organization.; Advisor: Robert Pfaltzgraff.; Committee: Ian Johnstone, and Anne Sartori.; Keyword: International relations.